If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8g + 4 + -6g = -5 Reorder the terms: 4 + 8g + -6g = -5 Combine like terms: 8g + -6g = 2g 4 + 2g = -5 Solving 4 + 2g = -5 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2g = -5 + -4 Combine like terms: 4 + -4 = 0 0 + 2g = -5 + -4 2g = -5 + -4 Combine like terms: -5 + -4 = -9 2g = -9 Divide each side by '2'. g = -4.5 Simplifying g = -4.5
| 16m=ft | | 4n^2-9=35 | | 8g+4-27=81 | | 192-3x=33x+16 | | k/4+4=6 | | 8g+4x-27=81 | | x-41=25 | | 15/x=0.5 | | 3x^2-8x-24=-8 | | [3x+2]=8 | | 2x+3a-6=19 | | 5-2x+7x=-2(-8x+3) | | 2x-10=2-x | | -.75x+2=11 | | 2a+2=a-1 | | x-10=x-2 | | n^2-14=-5n | | -600+40x=-480 | | 7(2x+4)=6(x+12) | | 2x^2-6xy-56y^2=0 | | 3-2(x+4)=12 | | (x+4)/(2x-5)=0 | | 0.31(70)+0.5x=0.3(70+x) | | 3-2(x-4)=12 | | 4(x-8)=-x+4+7x | | 2x+4(-2/4x+12/4)=8 | | x+4/2x-5=0 | | 4-7y+5y-1=2+3-y+y | | -4(-2+8k)-8=-192 | | x^4+2x-2Wx=0 | | x^4+2x-2ix=0 | | 2(4)-3(3)=17 |